John 13-17 viewed through liturgical spectacles - Suggit, J. N. (Neotestamentica, 1992)
Chapters 13-17 form an introduction to the Passion Narrative. To read them from the context of the eucharistic worship of the church helps later disciples see the liturgy as always involving a challenge to faithfulness and love, as contrasted with the action of Judas. The High-Priestly prayer of chapter 17 corresponds to the liturgical setting of chapter 13, and the allusions to baptism and eucharist confirm the disciples' understanding of their own identity resulting from their unity with Christ.